Close-to-Convexity of Convolutions of Classes of Harmonic Functions - Raj Kumar Garg; Jay M. Jahangiri (International Journal of Mathematics and Mathematical Sciences)
For j=1,2 and for positive integers m and n, we consider classes of harmonic functions fj=hj+gj¯, where g1(z)=znh1(z) and g2′(z)=znh2′(z) or g1′(z)=znh1′(z) and g2′(z)=zmh2′(z), and we prove that their convolution f1⁎f2=h1⁎h2+g1⁎g2¯ is locally one-to-one, sense-preserving, and close-to-convex harmonic in z<1.